A review of global initiatives to fight antibiotic resistance and recent antibiotics׳ discovery - Arpana Sagwal Chaudhary (Elsevier, 2016)
Data from across the world have shown an overall decline in the antibiotic pipeline and continually rising resistance to all first-line and last-resort antibiotics. The gaps in our knowledge of existing prevalence and mechanisms of antibiotic resistance (ABR) are all too well known. Several decades of antibiotic abuse in humans, animals, and agricultural practices have created health emergency situations and huge socio-economic impact. This paper discusses key findings of the studies conducted by several national and international collaborative organizations on the current state of affairs in ABR. Alongside, a brief overview of the antibacterial agents׳ discovery in recent years approved by the US FDA is discussed.